SOSIALISASI MENINGKATKAN BELAJAR BAHASA INGGRIS BERBASIS ENGLISH FOR SPECIFIC PURPOSES (ESP) DI MADRASAH MTs JANWARY NW BOROK LOTIM - Mul Muliadi; Evi Safitri Yulandari; Muhammad Wahyu Hadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
The aim of this Community Service (PKM) is to add insight and new experiences for teachers, especially for English teachers in MTs. Janwary NW Borok, East Lombok. The stages carried out in this PKM are: Managing all the completeness of the PKM, Identification of problems, Providing Assistance and Guidance, Monitoring and Evaluation of Implementation. The Community Service Program conducted by MTs. Janwary NW Borok Lombok Timur NTB obtained very satisfactory results as monitoring and evaluation had been carried out several times according to the set time. With the socialization and coaching through this PKM, students feel more confident in pronouncing English even though there are still many vocabulary words that have not been mastered, but students feel motivated and excited to develop their English skills.